2019
DOI: 10.1111/jocn.14993
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and its association with job satisfaction among nurses in a teaching hospital

Abstract: Aim and objectives To determine the prevalence of psychological distress and its association with job satisfaction among nurses in a teaching hospital in Malaysia. Background Nurses constitute the majority of health care workers, and, compared with other professions, nursing profession is highly stressful and, hence, a cause of anxiety and depression. This may affect nurses' job satisfaction. Method Using self‐administered questionnaires, Depression Anxiety and Stress Scale (DASS‐21) and Job Satisfaction Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 41 publications
10
52
3
1
Order By: Relevance
“…In this study, self-perceived health status of the GPT members was generally not positive, in keeping with the ndings from previous studies (Ghawadra et al, 2019;O li et al, 2004). Less than half of the participants reported good physical health, whereas approximately 55% perceived themselves to be mentally healthy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, self-perceived health status of the GPT members was generally not positive, in keeping with the ndings from previous studies (Ghawadra et al, 2019;O li et al, 2004). Less than half of the participants reported good physical health, whereas approximately 55% perceived themselves to be mentally healthy.…”
Section: Discussionsupporting
confidence: 91%
“…Our study provides a precise assessment of the relationship between health and job satisfaction, and the ndings are consistent with those reported in existing literature. GPT members' self-perceived physical and mental health were both signi cantly and positively associated with their job satisfaction (Faragher et al, 2005;Ghawadra et al, 2019;Bovier et al, 2009;Hwang, 2019). A meta-analysis by Faragher et al (2005) reported a much stronger relationship between job satisfaction and mental health, compared with the association between job satisfaction and physical health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have identified that job satisfaction is associated with age [18][19], marital status [20][21], clinical experience [19], educational level [18,22], and work patterns [19,23].…”
Section: Moderating Role Of Social Supportmentioning
confidence: 99%